Risk Factors for Nonunion of Distal Femur Fractures. Issue 4 (April 2023) - Cone, Ryan; Roszman, Alex; Conway, Yvonne; Cichos, Kyle; McGwin, Gerald; Spitler, Clay A.
Abstract : Objectives: To determine patient, fracture, and construct related risk factors associated with nonunion of distal femur fractures. Design: Retrospective cohort study. Setting: Academic Level I trauma center. Participants: Patients 18 years and older presenting with OTA/AO 33A and 33C distal femur fractures from 2004 to 2020. A minimum follow-up of 6 months was required for inclusion. OTA/AO 33B and periprosthetic fractures were excluded, 438 patients met inclusion criteria for the study. Main Outcomes: The primary outcome of the study was fracture nonunion defined as a return to the OR for management of inadequate bony healing. Patient demographics, comorbidities, injury characteristics, fixation type, and construct variables were assessed for association with distal femur fracture nonunion. Secondary outcomes include conversion to total knee arthroplasty, surgical site infection, and other reoperation. Results: The overall nonunion rate was 13.8% (61/438). The nonunion group was compared directly with the fracture union group for statistical analysis. There were no differences in age, sex, mechanism of injury, Injury Severity Score, and time to surgery between the groups. Lateral locked plating characteristics including length of plate, plate metallurgy, screw density, and working length were not significantly different between groups. Increased body mass index [odds ratio (OR), 1.05], chronic anemia (OR, 5.4), open fracture (OR, 3.74), and segmental bone loss (OR, 2.99) were independently associated with nonunion. Conversion to total knee arthroplasty (TKA) ( P = 0.005) and surgical site infection ( P < 0001) were significantly more common in the nonunion group. Conclusion: Segmental bone loss, open fractures, chronic anemia, and increasing body mass index are significant risk factors in the occurrence of distal femoral nonunion. Lateral locked plating characteristics did not seem to affect nonunion rates. Further investigation into the prevention of nonunion should focus on fracture fixation constructs and infection prevention. Level of Evidence: Prognostic Level III. See Instructions for Authors for a complete description of levels of evidence.